Can IQ predict parent-reported behavioral and emotional problems in children with neurological deficiencies?. (March 2017) - Peijnenborgh, Janneke C.A.W.; van Abeelen, Sandra A.M.; Hurks, Petra P.M.; Laridon, Annick M.; Klinkenberg, Sylvia; Aldenkamp, Albert P.; Vles, Johan S.H.; Hendriksen, Jos G.M.
Abstract: Objective: The aim of the current study was to investigate whether total intelligence scores (FSIQ) and/or a discrepancy in intelligence can predict behavioral or emotional problems in children with neurological deficiencies. Method: The population consists of children with neurological deficiencies ( N = 610, ranging from 6 to 17 years), referred due to concerns on the (educational) development of the child to a tertiary outpatient clinic. All children were tested with the Dutch Wechsler Intelligence Scale for Children – third edition (WISC-III-NL). A VIQ-PIQ discrepancy score was calculated by subtracting the performance capacities of the verbal capacities. The effects of demographic variables, FSIQ, and the VIQ-PIQ discrepancy on two parent-rated questionnaires measuring behavior and emotions in children were analyzed with linear and logistic regression models. Results and conclusion: The VIQ-PIQ discrepancy was not predictive of behavioral or emotional problems recorded on the above-mentioned parent-rated questionnaires. The FSIQ score, age, and sex were predictive to some extent: increases in age and FSIQ led to a decrease of reported problems, and boys showed more problems than girls. Children with neurological deficiencies had on average significantly higher verbal capacities than performance capacities, in line with the neuropsychological principle that language survives brain damage whereas performance capacities are more affected. Highlights: Verbal IQ is higher than performance IQ in children with neurological deficiencies. A discrepancy in IQ cannot predict behavioral or emotional problems. The higher the IQ, the lower the parent-reported behavioral or emotional problems.